In planta evaluation of different bacterial consortia for the protection of tomato plants against Alternaria spp. infection and Alternaria toxins presence in fruits - Giorni, Paola; Bulla, Giulia; Bellotti, Gabriele; Antinori, Maria Elena; Guerrieri, Maria Chiara; Fiorini, Andrea; Bertuzzi, Terenzio; Puglisi, Edoardo (Frontiers in Horticulture, 2024)
Four Plant Growth-Promoting Rhizobacteria (PGPR) consortia were assembled based on their plant growth-promoting (PGP) traits and biocontrol properties, previously characterized in vitro, and tested to protect tomato plants against Alternaria spp. infections. Results indicated that PGPR consortia significantly reduced Alternaria disease severity on tomato plants. Consortia C2 and C3 were particularly effective, demonstrating disease control rates similar to or exceeding those achieved with full-dose chemical fungicides. Furthermore, PGPR treatments markedly decreased fungal colonization in both leaves and fruits, with the best performing consortia reducing fungal presence by up to 98% shortly after inoculation in the short term. Only tenuazonic acid (TeA) was detected among the tested mycotoxins, and its levels were significantly lower in fruits from PGPR-treated plants. The combination of PGPR consortia with a reduced dose of fungicide also showed promising results, indicating a synergistic effect in controlling both fungal spread and mycotoxin production in the long run. Findings support the potential of PGPR as sustainable alternative to chemical fungicides, enhancing plant health while reducing environmental impact, aligning with current agricultural policies.